2014
DOI: 10.1080/09168451.2014.943650
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of RhoA promotes the proliferation and migration of cervical cancer cells

Abstract: The pro-oncogenic role of RhoA has been well identified in other cancers, but rarely in cervical cancer (CC), one of the main causes of cancer-related death in women. In the present study, we identified the overexpression of RhoA and its downstream effectors, ROCK-1 and ROCK-II, in CC specimens using western blotting. Then, we determined the effect of RhoA on the proliferation and migration of Hela cells, one of CC cell lines, by upregulating or downregulating the RhoA expression in Hela cells. We found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…based on a number of studies, upregulated RhoA is associated with tumor progression in different types of cancer (33)(34)(35) and RhoA activation promotes the migration of cervical, colon and hepatocellular carcinoma (36)(37)(38). However, significantly downregulated expression of RhoA was demonstrated in human conventional RCC compared to that in normal kidney tissues (17) and activated RhoA has specifically been shown to inhibit the migration of breast and prostate cancer (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…based on a number of studies, upregulated RhoA is associated with tumor progression in different types of cancer (33)(34)(35) and RhoA activation promotes the migration of cervical, colon and hepatocellular carcinoma (36)(37)(38). However, significantly downregulated expression of RhoA was demonstrated in human conventional RCC compared to that in normal kidney tissues (17) and activated RhoA has specifically been shown to inhibit the migration of breast and prostate cancer (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylated FAK and Akt trigger its downstream effectors including Rho families (Zhao et al, 2011). The Rac1 and RhoA-GTP downstream migratory protein controls the migration of cell by activating the development of cell-membrane protrusion filopodia at the boundary of the migrating side (Vega and Ridley, 2008;Liu et al, 2014). During the movement of cells, filopodia and lamellipodia increase and are required in migration and metastasis of cancer (Machesky, 2008;Dirat et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Rho family of small guanosine triphosphatases (GTPases), has been reported to play a crucial role in reorganization of actin and the formation of filopodia. The expression level of Rac1 and RhoA were found to be increased in several cancers including cervical cancer (Kamai et al, 2004;Liu et al, 2014). Upon the activation of Rac1 and RhoA, cancer cells migration are enlarged (Vega et al, 2008;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Using HiPerfect (Qiagen) as the transfection reagent, we have shown that siRNA 52 mediated Rho A knockdown results in the inhibition of actin stress fiber formation in endothelial (Huvec) cells (Kumar et al, 2011). Rho A is also known to be important in the proliferation of cervical cancer cells (Liu et al, 2014). In two other studies reported from our laboratory, siRNA 26 targeting Aurorakinase B (AURK-B) in the prostate cancer cell line, PC3 (Addepalli et al, 2010), and the hepatocellular carcinoma cell line, HepG2 , was reported.…”
Section: D2c As An Sirna Carrier For Anti Cancer Applicationmentioning
confidence: 99%